Regulation of skeletal muscle mitochondrial activity by thyroid hormones: focus on the “old” triiodothyronine and the “emerging” 3,5-diiodothyronine - Lombardi, Assunta; Moreno, Maria; De Lange, Pieter; Iossa, Susanna; Busiello, Rosa Anna; Goglia, Fernando (Frontiers in Physiology, 2015)
3,5,3'-triiodo-L-thyronine (T3) plays a crucial role in regulating metabolic rate and fuel oxidation; however, the mechanisms by which it affects whole-body energy metabolism are still not completely understood. Skeletal muscle (SKM) plays a relevant role in energy metabolism and responds to thyroid state by remodeling the metabolic characteristics and cytoarchitecture of myocytes. These processes are coordinated with changes in mitochondrial content, bioenergetics, substrate oxidation rate, and oxidative phosphorylation efficiency. Recent data indicate that "emerging" iodothyronines have biological activity. Among these, 3,5-diiodo-L-thyronine (T2) affects energy metabolism, SKM substrate utilization, and mitochondrial functionality. The effects it exerts on SKM mitochondria involve more aspects of mitochondrial bioenergetics; among these, respiratory chain activity, mitochondrial thermogenesis, and lipid-handling are stimulated rapidly. This minireview focuses on signaling and biochemical pathways activated by T3 and T2 in SKM that influence the above processes. These novel aspects of thyroid physiology could reveal new perspectives for understanding the involvement of SKM mitochondria in hypo- and hyperthyroidism.